Shannon entropy on near-infrared spectroscopy for nondestructively determining water content in oil palm - Inna Novianty; Walidatush Sholihah; Gema Parasti Mindara; Muhammad Iqbal Nurulhaq; Anifatul Faricha; Rismen Sinambela; Pradeka Brilyan Purwandoko; Muhammad Achirul Nanda (Institute of Advanced Engineering and Science, 2023)
Indonesia is the world’s largest producer of palm oil. To preserve its competitive advantages, the Indonesian oil palm sector must expand high-quality palm oil output. In oil palm quality control, the water content is a crucial parameter as it can be used as a reference to determine the right harvest time. Thus, this study proposed a near-infrared (NIR) spectroscopy as a fast and non-destructive analysis to assess oil palm water content. NIR spectra were processed using Shannon entropy to describe the characteristics at each wavelength. In this study, oil palm fruit samples at various maturity levels were collected with eight different maturity fractions. Based on the analysis, the Shannon entropy value is closely related to any changes in the water content of palm oil. The entropy value has a decreasing trend as the water content increases. The proposed technique can predict the water content of an oil palm with satisfactory performance with values of 0.9746 of coefficient of determination (R2) and 2,487 of root mean square error (RMSE). Application of this model will lead to a fast and accurate prediction system related to oil palm water content.